2000
DOI: 10.3317/jraas.2000.007
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical strain-induced human vascular matrix synthesis: The role of angiotensin II

Abstract: Introduction: Reduced vascular compliance in patients with hypertension results from an increase in extra-cellular matrix (ECM) protein deposition in blood vessels. At least two key factors, namely mechanical strain and neurohumoral mediators, for example Angiotensin II (Ang II), promote fibrogenesis within vessel walls; however potential interactions between these have not been clearly defined. This work examined the direct effect of mechanical strain on matrix mRNA expression and protein synthesis by human v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 19 publications
2
24
0
1
Order By: Relevance
“…27 Numerous studies have demonstrated that angiotensin II through AT1 receptor induces VSM cell proliferation and hypertrophy and has an essential role in extracellular matrix expansion. [29][30][31][32] Furthermore, Candesartan and cavernous tissue in SHR JE Toblli et al cell culture, animal models and clinical studies have supported the idea that AT1 receptor activation causes vascular superoxide release in vitro and in vivo leading to impairment of endothelium-dependent vasodilation. 33,34 In agreement with these findings, inhibition of AT1 receptor activation by AT1 receptor antagonist or ACE inhibitors improves endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 96%
“…27 Numerous studies have demonstrated that angiotensin II through AT1 receptor induces VSM cell proliferation and hypertrophy and has an essential role in extracellular matrix expansion. [29][30][31][32] Furthermore, Candesartan and cavernous tissue in SHR JE Toblli et al cell culture, animal models and clinical studies have supported the idea that AT1 receptor activation causes vascular superoxide release in vitro and in vivo leading to impairment of endothelium-dependent vasodilation. 33,34 In agreement with these findings, inhibition of AT1 receptor activation by AT1 receptor antagonist or ACE inhibitors improves endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 96%
“…In experimental models of hypertension, including suprarenal abdominal aorta constriction, ANG II acting directly and/or indirectly via the synthesis of peptide growth factors EGF and TGF-␤ significantly influenced vascular and cardiac remodeling (10,22,29,30,33,35,40). On the basis of these observations, we performed in vitro experiments to assess the impact of ANG II, EGF, and TGF-␤ 1 on nestin expression in cultured vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…Still, many challenges remain and are currently being addressed, particularly with regard to the improvement of graft mechanical properties in a limited period. In order to develop a patent tissue-engineered blood vessel that grossly resembles native tissue, required culture times in most studies exceed 8 weeks [29, 30]. Tissue-engineered blood vessels are not likely to be used in emergency situations because of the time necessary to allow for cell expansion, extracellular matrix production and organization, and attainment of desired mechanical strength.…”
Section: Discussionmentioning
confidence: 99%